2018
DOI: 10.1007/s11548-018-1761-3
|View full text |Cite
|
Sign up to set email alerts
|

In vivo estimation of target registration errors during augmented reality laparoscopic surgery

Abstract: PurposeSuccessful use of augmented reality for laparoscopic surgery requires that the surgeon has a thorough understanding of the likely accuracy of any overlay. Whilst the accuracy of such systems can be estimated in the laboratory, it is difficult to extend such methods to the in vivo clinical setting. Herein we describe a novel method that enables the surgeon to estimate in vivo errors during use. We show that the method enables quantitative evaluation of in vivo data gathered with the SmartLiver image guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 24 publications
0
39
0
Order By: Relevance
“…A novel image-guided surgery system (SmartLiver) was designed for use in LLR through a programme of basic research and clinical development commissioned by the Wellcome Trust in partnership with the Department of Health (UK) [21,26,27,29].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A novel image-guided surgery system (SmartLiver) was designed for use in LLR through a programme of basic research and clinical development commissioned by the Wellcome Trust in partnership with the Department of Health (UK) [21,26,27,29].…”
Section: Methodsmentioning
confidence: 99%
“…Due to the lack of standardised methods for assessing IGS navigation accuracy [34], our group previously proposed a landmark based method which was also employed here [21,26]. In brief, distances between corresponding anatomical landmarks on laparoscopic images and the 3D liver model are measured and compared ( Fig.…”
Section: Comparison Of Manual and Semi-automatic Registrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Image guidance, and specifically augmented reality, has been proposed as a way to alleviate this problem and reduce the risk of complication . Most guidance systems use optical tracking . When using optical tracking, to ensure a free line‐of‐sight, markers must be placed on the distal end of the laparoscope, far from the optical center of its camera, thereby creating a lever‐arm effect, reducing system accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…1 Most guidance systems use optical tracking. [2][3][4][5] When using optical tracking, to ensure a free line-of-sight, markers must be placed on the distal end of the laparoscope, far from the optical center of its camera, thereby creating a lever-arm effect, reducing system accuracy. Our previous work has shown that an EM sensor placed at the proximal end of the laparoscope should provide higher system accuracy.…”
Section: Introductionmentioning
confidence: 99%